STUDI KUALITAS AIR UNTUK KESEHATAN IKAN DALAM BUDIDAYA PERIKANAN PADA ALIRAN SUNGAI KAMPAR KIRI - Syofyan, Irwandy; Usman, Usman; Nasution, Polaris (Jurnal Perikanan dan Kelautan, 2011)
This research is done on October 2010 at Kampar Kiri river stream area,Riau Province. The purpose of this research is to find out the influence of goldmines without license activity to water quality and fish health. The method used issurvey method by measuring environmental factors of territorial water. Theconcideration that used namely the estimation to the source of contamination andwaste burden accepted by territorial water of development of aquaculture. Asreference, here include water quality of Kampar River completely as RiauGovernor Decree no 23 in 2003 (that guidances on PP 82/2001), about allotmentand permanent quality of water at Kampar River, Riau Province. Meanwhile, thefish area sampled from pond and cage that existed in every development area.From this research is known that generally each the quality of river water for fishhealth in aquaculture is still in tolerance level. The result of measurement waterquality is the fulfill permanent quality of first class water except some ofparameters in development aquaculture area in distric, like Kampar kiri River andhall fish breeding (BBI) Teso. Mophologically, fish health that watched is still beoptimal.